(The Production of Aloe vera Powder Using Spray Dryer and Its Quality Characteristics) - -, Sumarsi; -, Lucyana; Anita, Fikti (Balai Besar Industri Agro, 1998)
A study on the production of Aloe Vera (Aloe Vera Linn) powder using spray dryer has been conducted. The fillers used were arabic gum 1%, CMC 1%and Carragenan 1%. Analysis done on the Aloe powder are moisture content, acidity (pH), amino acids, particle spread and viscosity. The moisture content and pH of Alue powder filled with arabic gum and CMC met the requirement of CTFA code TN. 001. It moisture content were 6.40 - 7,23%, while the pH 4-5. Aloe powder with carragen did not meet the above requirement. However the amino acid content in powder using carragen filler was almost the same as those of Aloe gel. Its particle size was also finer and therefore it is more soluble in water.